The Definition of Curriculum Areas in Occupational Health Psychology - Houdmont, Jonathan; Leka, Stavroula; Bulger, Carrie (Nottingham University Press, 2008)
Across the international educational landscape, numerous higher education institutions (HEIs) offer postgraduate programmes in occupational health psychology (OHP). These seek to empower the next generation of OHP practitioners with the knowledge and skills necessary to advance the understanding and prevention of workplace illness and injury, improve working life and promote healthy work through the application of psychological principles and practices. Among the OHP curricula operated within these programmes there exists considerable variability in the topics addressed. This is due, inter alia, to the youthfulness of the discipline and the fact that the development of educational provision has been managed at the level of the HEI where it has remained undirected by external forces such as the discipline’s representative bodies. Such variability makes it difficult to discern the key characteristics of a curriculum which is important for programme accreditation purposes, the professional development and regulation of practitioners and, ultimately, the long-term sustainability of the discipline. This chapter has as its focus the imperative for and development of consensus surrounding OHP curriculum areas. It begins by examining the factors that are currently driving curriculum developments and explores some of the barriers to such. It then reviews the limited body of previous research that has attempted to discern key OHP curriculum areas. This provides a foundation upon which to describe a study conducted by the current authors that involved the elicitation of subject matter expert opinion from an international sample of academics involved in OHP-related teaching and research on the question of which topic areas might be considered important for inclusion within an OHP curriculum. The chapter closes by drawing conclusions on steps that could be taken by the discipline’s representative bodies towards the consolidation and accreditation of a core curriculum.